Implementing Marketing Strategies in the Tax Preparation Business - Razak, Ismail (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
Tax preparation businesses are crucial in helping individuals and companies understand and comply with complex tax regulations. However, tax preparation businesses need to adopt relevant and innovative marketing strategies in the digital era and with increasing competition. This research aims to explore and analyze the implementation of effective marketing strategies in the context of tax preparation business. This research uses a qualitative approach with descriptive methods. The research results show that implementing marketing strategies in the tax preparation business positively impacts increasing brand presence, attracting new customers, and achieving business growth. Using a combination of digital and offline marketing strategies, including content marketing and an active presence on social media, has proven effective in reaching a wider audience. SMART goal setting and KPI measurement help measure marketing campaigns' success, while data analysis through tools like Google Analytics provides valuable insights into customer behavior and market trends. Furthermore, calculating return on investment (ROI) allows businesses to allocate budgets efficiently, identify the most effective marketing channels, and improve the sustainability of growth.